The onset of shear modes in the high frequency spectrum of simple disordered systems: current knowledge and perspectives. Issue 7 (23rd March 2016) - Cunsolo, Alessandro; Suvorov, Alexey; Cai, Yong Q.
Abstract : Nearly two decades of thorough inelastic X-ray scattering (IXS) studies of transverse-like excitation in the spectrum of simple amorphous materials are reviewed. Particular attention is given to the case of liquid water and other prototypical samples, through discussion of both solved and still open issues. The perspectives opened up by the development of next generation IXS instruments with unprecedented contrast and resolution bandwidth are briefly illustrated.